Perlindungan Terhadap Pekerja Anak di Indonesia: Kajian Historis - Ridho Rokamah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to examine efforts to protect child laborers in Indonesia from a historical perspective, by tracing the development of policies and regulations from the colonial period to the reformation era. This study uses a qualitative method with a historical-normative approach, through the study of documents, legislation, and relevant literature. The results show that the issue of child labor has been a concern since the Dutch East Indies era, but comprehensive legal protection has only begun to develop after independence. The Manpower Act and the ratification of international conventions have become important milestones in the strengthening of children's rights. However, the challenge of implementation is still high due to socio-economic factors and weak law enforcement. This study emphasizes the importance of synergy between policy, education, and public awareness in eliminating the practice of child labor in a sustainable manner.